Antifungal Activity against Fusarium culmorum of Stevioside, Silybum marianum Seed Extracts, and Their Conjugate Complexes - Laura Buzón-Durán; Jesús Martín-Gil; María del Carmen Ramos-Sánchez; Eduardo Pérez-Lebeña; José Luis Marcos-Robles; Ángel Fombellida-Villafruela; Pablo Martín-Ramos (MDPI AG, 2020)
Fusarium head blight (FHB) is a disease that poses a major challenge in cereal production that has important food and feed safety implications due to trichothecene contamination. In this study, the effect of stevioside-a glycoside found in the leaves of candyleaf (Stevia rebaudiana Bertoni)-was evaluated in vitro against Fusarium culmorum (W.G. Smith) Sacc., alone and in combination (in a 1:1 molar ratio) with polyphenols obtained from milk thistle seeds (Silybum marianum (L.) Gaertn). Different concentrations, ranging from 32 to 512 µg·mL−1, were assayed, finding EC50 and EC90 inhibitory concentrations of 156 and 221 µg·mL−1, respectively, for the treatment based only on stevioside, and EC50 and EC90 values of 123 and 160 µg·mL−1, respectively, for the treatment based on the stevioside-polyphenol conjugate complexes. Colony formation inhibition results were consistent, reaching full inhibition at 256 µg·mL−1. Given that synergistic behavior was observed for this latter formulation (SF = 1.43, according to Wadley's method), it was further assessed for grain protection at storage, mostly directed against mycotoxin contamination caused by the aforementioned phytopathogen, confirming that it could inhibit fungal growth and avoid trichothecene contamination. Moreover, seed tests showed that the treatment did not affect the percentage of germination, and it resulted in a lower incidence of root rot caused by the pathogen in Kamut and winter wheat seedlings. Hence, the application of these stevioside-S. marianum seed extract conjugate complexes may be put forward as a promising and environmentally friendly treatment for the protection of cereal crops and stored grain against FHB.